Tinjauan Penyaluran Kredit Usaha Rakyat (KUR) Kepada Nasabah Pada PT Bank Syariah Indonesia KCP Bogor Pomad - Susan Susanti; Sujana Sujana; Saefudin Zuhdi; Bayu Prasetyo Soedargo (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Financing is the provision of money or bills that are equated based on an agreement or agreement between the bank and another party that requires the party to be financed to return the money or bill according to a certain period of time with compensation or profit sharing. Based on the Regulation of the Minister of Finance (PMK) No.135 / PMK.05 / 2008 dated December 5, 2008, article 5 concerning the People's Business Credit (KUR) guarantee facility, it is stated that the People's Business Credit (KUR) is a program issued by the government, but the source of funds comes entirely from bank funds. People's Business Credit is financing for Micro, Small and Medium Enterprises (MSMEs) in the form of Working Capital Credit (KMK) and or Investment Credit (KI). The purpose of this financing research is to determine the provisions for distributing people's business credit financing, to determine the stages of distributing KUR financing and to determine the obstacles experienced by PT Bank Syariah Indonesia KCP Bogor Pomad in the process of distributing people's business credit financing and solutions to each obstacle that occurs in the process of distributing people's business credit financing at PT Bank Syariah Indonesia KCP Bogor Pomad. The results of the study indicate that the process of distributing people's business credit at PT Bank Syariah is good and in accordance with the company's Standard Operating Procedure (SOP). In the process of distributing financing, there are terms and conditions in advance when you want to apply for super micro KUR financing, micro KUR and small KUR at PT Bank Syariah Indonesia. By collecting requirements in the form of documents or other requirements that have been determined by the bank before applying for the financing. After the terms and conditions have been met, prospective customers must follow the stages in the KUR financing distribution process until the final decision on the disbursement of financing that will be given by the bank. Keywords: Financing, Distribution of People's Business Credit